Penerapan Aplikasi PLN Mobile Dalam Meningkatkan Pelayanan Pelanggan PLN ULP Bojonegoro Kota - Siti Akromah; Indah Respati Kusumasari (Jurnal Masyarakat Mengabdi Nusantara, 2023)
In this digital era, the Perusahaan Listrik Negara (PLN) continues to innovate in meeting people's electricity needs by presenting an application called PLN Mobile. This application is a digital-based electricity needs service provider application developed directly by PLN. On an ongoing basis PT PLN continues to provide feature updates and various other services to customers since this application was launched. The PLN Mobile application has various features, such as buying tokens (prepaid customers), paying electricity bills (postpaid customers), complaints about electricity, marketplaces, etc. With the PLN Mobile application, it helps meet people's electricity needs online without having to go to the PLN Customer Service Unit office.